The Role of Dormitory Supervisors as Agents of Islamic Character Development through Student Discipline Enforcement - Desva Usifa; Ardi Satrial; Nurhayati Nurhayati (Ahlussunnah: Journal of Islamic Education, 2026)
This study aims to analyze the role of dormitory supervisors as agents of Islamic character transformation through the enforcement of student discipline in an Islamic boarding school environment. The study employed a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that dormitory supervisors play a significant role in fostering Islamic character through role modeling, habituation, supervision, and a dialogic-persuasive approach to discipline enforcement. Discipline was found to function not only as a mechanism for behavioral control but also as a means of internalizing Islamic values that promote responsibility, rule compliance, independence, and self-control among students. Furthermore, the integration of modern caregiving practices with local pesantren values strengthens the effectiveness of character development efforts. This study highlights that a dialogic-persuasive approach to discipline enforcement contributes to the transformation of students’ Islamic character and may serve as a model for strengthening character education in Islamic boarding schools.